CONTEXTUALIZING HADITH ON FEMALE LEADERSHIP: JASSER AUDA’S MAQASHID AL-SHARIAH APPROACH - Ahmad Fariza Abdullah; Luluk Sakilah (Al-Dhikra: Jurnal Studi Quran dan Hadis, 2026)
This paper re-examines the hadith concerning female leadership through a contextualization process based on Jasser Auda’s maqashid al-shariah, aiming to discover a meaning relevant to contemporary society. The study focuses on the hadith regarding the misfortune of a people who entrust their affairs to a woman a text often interpreted literally, resulting in normative restrictions that do not always align with current socio-political realities. Employing a literature review methodology, the research analyzes relevant texts using the maqashid approach, which offers an evaluative framework prioritizing justice, human dignity, and public interest as benchmarks for assessing the suitability of an interpretation. The article demonstrates that a literal interpretation fails to meet the teleological demands of maqashid, particularly when such an interpretation potentially hinders beneficial social and political participation. The analysis reveals that a contextual reading focused on achieving public interest provides a stronger normative foundation while maintaining respect for traditional sources. Ultimately, the paper asserts that the maqashid approach serves as a hermeneutic bridge connecting textual authority with the needs of contemporary society, thereby creating space for the construction of Islamic law that is more just, inclusive, and consistent with the fundamental principles of Sharia.